A comparative study of temperature of mass concrete placed in August and November based on on-site measurement. (December 2021) - Hu, Yehong; Chen, Jin; Zou, Feng; He, Meng; Mao, Jianguo; Liu, Xinglin; Zhou, Canjun; Yuan, Zhongxia
Abstract: In this study, on-site temperature measurements lasted for 29 days and 16 days, were carried out for a mat foundation and the slab of first floor of the same building. The measurement data revealed temperature evolution at different depth of mass concrete placed in August and November. For the mass concrete placed in August, due to large diurnal temperature range (DTR), low humidity and high initial temperature of fresh concrete, there were not only a sharp temperature increase in the middle of mass concrete within 48 h after placement, but also a substantial overrun of temperature difference between core and surface, especially at position of larger thickness. Furthermore, evaporation due to weak insulation and low humidity reduced degree of hydration in the near surface layer at early stage to result in low compressive strengthen as validated by compressive strength test on concrete cubes. For the mass concrete placed in November, it is found that the curing procedure adopted was largely adequate and the temperature evolution at different depth of mass concrete was approximately synchronous, except that soaking of cotton felt created a short period of temperature drop at initial stage in surface layer. Based on this study and also a comparison on curing and temperature control recommended both in Chinese code and ACI (American Concrete Institute) standards, it is proposed that Chinese code should also incorporate water evaporation control, since in Northwest China where the relative humidity can be very low, DTR is very large and temperature can be high enough to induce substantial amount of evaporation in certain months.